Hall effect on thermosolutal instability in a Maxwellian viscoelastic fluid in porous medium - Sharma, R.C.; Kumar, P. (Archives of Mechanics, 1996)
Thermosolutal instability in a Maxwellian viscoelastic fluid in porous medium is studied to include the effect of Hall current. For stationary convection, the Maxwellian viscoelastic fluid behaves like an ordinary Newtonian fluid and stable solute gradient is found to have stabilizing effect, whereas Hall currents and medium permeability are found to have destabilizing effects on the system. The sufficient conditions for the non-existence of overstability are also obtained.